Firm profitability and expected stock returns : evidence from Latin America (2020)
Despite their higher valuation ratios, larger size, and higher investment needs, profitable firms outperform, in both raw and risk-adjusted returns, unprofitable firms in Latin America. The positive effect of firm profitability on stock returns is pervasive in univariate and bivariate sorts, panel regressions, across sub-regional markets, and among small and large stocks. A five-factor model that includes market, size, distress, profitability, and investment factors prices profitability portfolios better than other popular factor models. Five-factor alphas of profitability portfolios tend to be lower and less statistically significant, both individually and collectively, than alphas from other three widely-used pricing models.